PENGARUH HARGA, LOKASI DAN FASILITAS TERHADAP KEPUTUSAN PEMBELIAN PADA PERUMAHAN GRAND MUTIARA VILLAGE KARAWANG - Iskandar, Dede Nur; Sumiyati, Sumiyati (Universitas Mercu Buana, 2019)
ABTSTRACT. The purpose of this research is to find the influence of price , location and facilities of the decision the purchase of Perumahan Grand Mutiara Village Karawang. Technique the sample collection done with purposive sampling .In this research sample taken 200 people. Data taken through a method of the questionnaire and the technique analysis using regression multiple regression linear analysis. The research results show that in partial test t indicated that the perception of price, location, and facilities have an significant of the purchase decision. Based on the simultaneous (F test ) is shown that the variable perception of price, location, and facilities have impact positive and significant to purchase decision at Perumahan Grand Mutiara Village Karawang. Biggest value coefficient standardized, variables of location have dominant impact to purchase decision at Perumahan Grand Mutiara Village Karawang.